Role of food and nutrition and prevention in pathogenesis of the arterial occlusive disease - Patricia Reba (Kazimierz Wielki University, 2020)
<p class="17" style="margin-top: 0,0000pt; margin-bottom: 0,0000pt; text-autospace: ideograph-numeric; mso-pagination: none; text-align: justify; text-justify: inter-ideograph; vertical-align: baseline; line-height: 150%;" align="justify">Admission <p class="17" style="margin-top: 0,0000pt; margin-bottom: 0,0000pt; text-autospace: ideograph-numeric; mso-pagination: none; text-align: justify; text-justify: inter-ideograph; vertical-align: baseline; line-height: 150%;" align="justify">          Atherosclerosis is a chronic inflammatory disease of complex etiopathogenesis. Improper diet, genetic predisposition, lack of physical activity, and smoking are just a few of the major factors contributing to the development of atherosclerotic plaque. Diet in atherosclerosis, treatment is based. Antiatherosclerotic diet is one of many components, which should provide not only the treatment of such a state, but primarily prevention. Accordingly, balanced nutrition regimen can reduce cholesterol synthesis in the liver, which contributes to the development of atherosclerosis. Limiting the intake of trans fatty acids and saturated fatty acids allows for inhibiting the development of atherosclerotic plaque. <p class="17" style="margin-top: 0,0000pt; margin-bottom: 0,0000pt; text-autospace: ideograph-numeric; mso-pagination: none; text-align: justify; text-justify: inter-ideograph; vertical-align: baseline; line-height: 150%;" align="justify">Aim <p class="17" style="margin-top: 0,0000pt; margin-bottom: 0,0000pt; text-autospace: ideograph-numeric; mso-pagination: none; text-align: justify; text-justify: inter-ideograph; vertical-align: baseline; line-height: 150%;" align="justify">The aim of the study is to analyze the role of food and nutrition in the prevention and pathogenesis of atherosclerosis of the lower extremities. <p class="17" style="margin-top: 0,0000pt; margin-bottom: 0,0000pt; text-autospace: ideograph-numeric; mso-pagination: none; text-align: justify; text-justify: inter-ideograph; vertical-align: baseline; line-height: 150%;" align="justify">Material and methods <p class="17" style="margin-top: 0,0000pt; margin-bottom: 0,0000pt; text-autospace: ideograph-numeric; mso-pagination: none; text-align: justify; text-justify: inter-ideograph; vertical-align: baseline; line-height: 150%;" align="justify">A review of available literature. <p class="17" style="margin-top: 0,0000pt; margin-bottom: 0,0000pt; text-autospace: ideograph-numeric; mso-pagination: none; text-align: justify; text-justify: inter-ideograph; vertical-align: baseline; line-height: 150%;" align="justify">Results <p class="17" style="margin-top: 0,0000pt; margin-bottom: 0,0000pt; text-autospace: ideograph-numeric; mso-pagination: none; text-align: justify; text-justify: inter-ideograph; vertical-align: baseline; line-height: 150%;" align="justify">          Adequate intake of potassium in the diet contributes significantly to reducing the risk of atherosclerosis and hypertension. Potassium determines many important functions in the body.Due to the fact that the monounsaturated fatty acids reduce LDL cholesterol levels, the proportion should be in the diet increased to 15% and for the secondary prevention of up to 20%. In the prevention of atherosclerosis is very important to maintain an appropriate ratio of omega-6 to omega-3 ratio is absolutely should be no more than 4. It is extremely important in the diet because distorted value for the benefit of omega-6 favors the formation of atherosclerotic lesions.respective supply of carbohydrates also has a huge impact on the development of atherosclerotic lesions. The recommended amount of antiatherosclerotic dietary up to 60% provided that the people do not apply to such ailments as hypertension, overweight or obesity, elevated fasting blood sugar levels, decreased HDL cholesterol and elevated triglycerides. <p class="17" style="margin-top: 0,0000pt; margin-bottom: 0,0000pt; text-autospace: ideograph-numeric; mso-pagination: none; text-align: justify; text-justify: inter-ideograph; vertical-align: baseline; line-height: 150%;" align="justify">Conclusions <p class="17" style="margin-top: 0,0000pt; margin-bottom: 0,0000pt; text-autospace: ideograph-numeric; mso-pagination: none; text-align: justify; text-justify: inter-ideograph; vertical-align: baseline; line-height: 150%;" align="justify">General nutritional recommendations play the role of a signpost, which you should use expecting to improve health. It should be noted, however, that is not all. Nutritional prevention is significant, but equally important is lifestyle modification. Atherosclerotic diet is an important part of the treatment of the disease and prevent further growth of atherosclerotic plaque. Atherosclerosis requires the use of low-fat diet that is necessary to beat high blood cholesterol levels.